Steady State Response of a Non-linear Mechanical System Provided with an Impact Vibration Absorber - Kumar, Sunil J. (My University, 1966)
An investigation of the steady state response of a non-linear system provided with an impact vibration absorber is made. The term non-linear in the present case refers to a system in which the spring restoring force is bi-linear./p>
The effect of two main parameters viz. clearance d o (i.e. the free path of travel of the mass particle) and mass ratio μ = m/M (i.e. mass ratio between the mass particle and the primary system) on amplitude of vibration of the system has been investigated experimentally over a range of frequency.
A numerical analysis of the problem is made with the aid of a digital computer to supplement the experimental results.
It has been found that with proper choice of parameters an impact vibration absorber is effective in reducing vibration level of a nonlinear system undergoing sinusoidal excitation.
Keywords: investigation, non-linear, vibration, absorber, bi-linear